(untitled) (INNOVATIVE ECONOMY, 2020)
Zaiachkovska H.A. PRODUCT STRATEGY OF PUBLIC AUTHORITIES IN THE MARKET OF INBOUND TOURISM IN UKRAINE Purpose. The aim of the article is to disclosure the essence of the main components of the product strategy of public authorities at the macro and meso levels in the market of inbound tourism in Ukraine. Methodology of research. The research uses dialectical and systemic approaches, according to which the elements of the product strategy of public authorities at the macro and meso levels are considered in the relationship and interdependence. The methods of formalization, structural synthesis and scientific generalization are used in the development of measures of commodity, price and communication strategies of public authorities in the course of the research. Findings. The product strategy of public authorities for the development of inbound tourism to Ukraine has been developed and its components have been identified. The factors influencing the choice of the type of standardized or adapted marketing strategy are identified. It is established that the task of the product strategy is to ensure the rational use of tourist and recreational resources in Ukraine; the pricing strategy of public authorities provides for the regulation of prices for different categories of tourists and for stays in protected areas; communication strategy is aimed at promoting national and regional tourism products, brand formation and tourism image of Ukraine and its destinations. The essence of marketing tools that should be used in the implementation of product, sales and communication strategies is highlighted. Originality. Proposals have been developed for the components of the product strategy of public authorities, their tasks and the use of marketing tools for their implementation. Practical value. The results of scientific developments and practical recommendations given in the article can be used by public authorities at the macro and meso levels in developing a product strategy for the inbound tourism market in Ukraine. Key words: product strategy, commodity strategy, price strategy, communication strategy, public authorities, macro level, meso level.